THE FUNCTION OF THE STATE BOARD OF ACCOUNTANCY IN IMPROVING REPORTING STANDARDS IN CALIFORNIA. - Lamden, Charles W. (The Accounting Review, 1964)
Abstract In recent years the California State Board of Accountancy has devoted considerable time to various problems that are involved in improving reporting standards. The California Board of Accountancy consists of eight members comprising of five certified public accountants, two public accountants and one public member not licensed or registered by the Board. The Board has only those powers and duties conferred on it by the Accountancy Act. These powers and duties are required in the administration of the Act. The Accountancy Act empowers the Board to adopt the rules and regulations necessary to carry out its responsibilities. Upon analysis it is obvious that the rule involves almost all of the basic background in the theory of auditing. Thus, accountants must be familiar with the literature of the American Institute of Certified Public Accountants to understand the meaning of auditing standards and to keep abreast of the changing concepts related to these standards. Rules of professional conduct that have been established as a result of the authority vested in the Board, are found in Article 9, Chapter 1, Title 16 of the California Administrative Code.